A global genomic approach uncovers novel components for twitching motility-mediated biofilm expansion in Pseudomonas aeruginosa. Issue 11 (1st November 2018) - Nolan, Laura M.; Whitchurch, Cynthia B.; Barquist, Lars; Katrib, Marilyn; Boinett, Christine J.; Mayho, Matthew; Goulding, David; Charles, Ian G.; Filloux, Alain; Parkhill, Julian; Cain, Amy K.
Abstract : Pseudomonas aeruginosa is an extremely successful pathogen able to cause both acute and chronic infections in a range of hosts, utilizing a diverse arsenal of cell-associated and secreted virulence factors. A major cell-associated virulence factor, the Type IV pilus (T4P), is required for epithelial cell adherence and mediates a form of surface translocation termed twitching motility, which is necessary to establish a mature biofilm and actively expand these biofilms. P. aeruginosa twitching motility-mediated biofilm expansion is a coordinated, multicellular behaviour, allowing cells to rapidly colonize surfaces, including implanted medical devices. Although at least 44 proteins are known to be involved in the biogenesis, assembly and regulation of the T4P, with additional regulatory components and pathways implicated, it is unclear how these components and pathways interact to control these processes. In the current study, we used a global genomics-based random-mutagenesis technique, transposon directed insertion-site sequencing (TraDIS), coupled with a physical segregation approach, to identify all genes implicated in twitching motility-mediated biofilm expansion in P. aeruginosa . Our approach allowed identification of both known and novel genes, providing new insight into the complex molecular network that regulates this process in P. aeruginosa . Additionally, our data suggest that the flagellum-associated gene products have a differential effect on twitching motility, based on whether components are intra- or extracellular. Overall the success of our TraDIS approach supports the use of this global genomic technique for investigating virulence genes in bacterial pathogens.